Thermophiles: potential chassis for lignocellulosic biorefinery. Issue 6 (June 2022) - Jiang, Yujia; Jiang, Wankui; Xin, Fengxue; Zhang, Wenming; Jiang, Min
Abstract : Lignocellulosic thermophiles can speed up lignocellulose hydrolysis and promote efficient degradation, but limited genetic tools and heavy metabolic burden narrow the spectrum of potential products. Constructing synthetic microbial consortia is a potential strategy to address this bottleneck and improves the efficiency of lignocellulosic biorefineries.